Valuation reports in the context of banking resolution: What are the challenges? - Martin F. Hellwig (Max Planck Institute for Research on Collective Goods, 2018)
The paper discusses the problem of valuation in bank resolution. In an overview over the most relevant principles of valuation theory, the paper notes the difficulties inherent in valuing risks and illiquidity in holding non-traded assets. Subsequently, the paper briefly reviews the resolution of Banco Popular Espa\~nol, and then discusses the need for clarification of the no-investor-worse-off principle, the relation between the price in a sale of business and the presumed outcome in an insolvency procedure, and the difficulties attached to assessing the value of an illiquid asset that is held. The paper concludes with a discussion of the need for time, for valuation and in resolution, warns against a moratorium on withdrawals and payouts, and argues that time pressures would be much reduced if funding in resolution was provided for.
Keywords: G21; G28; G33; 330; bank resolution; valuation; no-investor-worse-off principle; Banco Popular Espa\~nol